2014
DOI: 10.1002/poc.3338
|View full text |Cite
|
Sign up to set email alerts
|

Computational study of singlet and triplet sulfonylnitrenes insertion into the C―C or C―H bonds of ethylene

Abstract: Formation of N‐sulfonylaziridines, N‐ethylidenesulfonamides, N‐vinylsulfonamides and 4,5‐dihydro‐1,2,3‐oxathiazole 2‐oxides by the reaction of singlet and triplet trifluoromethyl‐, methyl‐ and tosylnitrenes with ethylene is studied computationally at the B3LYP/6‐311++G(d,p) level of theory in both gas phase and in solution. Singlet sulfonylnitrenes react with ethylene via [1 + 2]‐cycloaddition exothermically to give N‐sulfonylaziridines. Triplet sulfonylnitrenes are formed from the singlet ones by the intersys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 46 publications
(110 reference statements)
0
2
0
Order By: Relevance
“…6,23 Recently, we confirmed that such transformation has an activation barrier of as low as 2 kcal mol À1 . 21 That means that the formation of triplet nitrene is, apparently, the predominant if not the only process of transformation of the singlet nitrene and the two processes should occur with the 3b and 4). A 'rise-decayrise' profile of the 1323 cm À1 curve in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…6,23 Recently, we confirmed that such transformation has an activation barrier of as low as 2 kcal mol À1 . 21 That means that the formation of triplet nitrene is, apparently, the predominant if not the only process of transformation of the singlet nitrene and the two processes should occur with the 3b and 4). A 'rise-decayrise' profile of the 1323 cm À1 curve in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…6 This S 1 state decays to produce the singlet nitrene 1 (2-C 10 H 7 SO 2 N) as a short-lived species (t S E 0.70 AE 0.30 ns in CCl 4 ) that decays to the lower-energy and longer-lived triplet nitrene 3 (2-C 10 H 7 SO 2 N). The triplet spin state is the ground state for sulfonyl nitrenes which has been proved both theoretically 6,19,21 and experimentally by ESR and IR spectroscopy in matrices at low temperature. 16,17,20 However, neither singlet nor triplet sulfonylnitrenes are global minima, because the most stable species are N-sulfonylimines RNSO 2 , which are formed with a large energy gain.…”
Section: Introductionmentioning
confidence: 94%